Pneumococcal Meningitis in Adults: A Prospective Nationwide Cohort Study Over a 20-year Period. (24th May 2021) - Koelman, Diederik L H; Brouwer, Matthijs C; ter Horst, Liora; Bijlsma, Merijn W; van der Ende, Arie; van de Beek, Diederik
Abstract: Background: The epidemiology and treatment of pneumococcal meningitis has changed with the implementation of conjugate vaccines and the introduction of adjunctive dexamethasone therapy. Methods: We analyzed episodes of community-acquired pneumococcal meningitis in adults (≥16 years) in the Netherlands, identified by the National Reference Laboratory for Bacterial Meningitis or treating physician between October 1, 1998, and April 1, 2002, and between January 1, 2006, and July 1, 2018. We studied incidence, pneumococcal serotypes, and clinical features. Predictors for unfavorable outcome (Glasgow Outcome Scale score 1–4) were identified in a multivariable logistic regression model. Two physicians independently categorized causes of death as neurological or systemic. Results: There were 1816 episodes in 1783 patients. The incidence of 7- and 10−7-valent pneumococcal conjugate vaccine serotypes decreased (from 0.42 to 0.06, P = .001; from 0.12 to 0.03 episodes per 100 000 population per year, P = .014). Incidence of nonvaccine serotypes increased (from 0.45 to 0.68, P = .005). The use of adjunctive treatment with dexamethasone increased and was administered in 85% of patients in 2018. In-hospital death occurred in 363 episodes (20%) and unfavorable outcome in 772 episodes (43%). Delayed cerebral thrombosis occurred in 29 patients (2%), of whom 15 patients (52%) died. Adjunctive dexamethasone therapy was associated with favorable outcome (adjusted odds ratio 2.27, P < .001), individual pneumococcal serotypes were not. Conclusion: Implementation of conjugate vaccines and adjunctive dexamethasone therapy have changed the incidence and outcome of pneumococcal meningitis in adults over the last two decades. Despite recent advances pneumococcal meningitis remains associated with a residual high rate of mortality and morbidity. Abstract : Progress has been made in the prevention and treatment of pneumococcal meningitis. The rate of morbidity and mortality is however still high, warranting continuous efforts in identifying new adjunctive treatments and pushing them forward into clinical trials.